Assessing the Moisture Transports Associated With Nocturnal Low-Level Jets in Continental South America - Braz, Dejanira Ferreira; Ambrizzi, Tércio; da Rocha, Rosmeri Porfírio; Algarra, Iago; Nieto, Raquel; Gimeno, Luis (Frontiers in Environmental Science, 2021)
Given the crucial role of low-level circulation to the convective events, this study presents a climatological characterization of moisture sources and sinks associated with the occurrence of nocturnal low-level jets (NLLJs) over South America. Six selected NLLJ cores are identified according to the jet index that considers the lower troposphere vertical wind speed shear at 00:00 local time (LT). The Lagrangian FLEXPART model were used to provide the outputs to track atmospheric air masses to determine the moisture sources and sinks for the NLLJ cores (Argentina, Venezuela, and regions of Brazil: south– Brazil-S, southeast– Brazil-SE, north– Brazil-N, and northeast – Brazil-NE). The analysis is based on 37 years (1980-2016) of the ERA-Interim reanalysis. We found that the NLLJ index is stronger in the warm periods of the year (Austral Spring and Summer) over the six selected regions. The NLLJ frequency is also higher in the warm months of the year, except in Brazil-NE, where it is very frequent in all months. In Brazil-NE the NLLJ also persists for 8 or more days, while other NLLJs frequently persist for one-two days. The NLLJs occupy a broad low-level layer (from 1000-700 hPa) and exhibit mean speed between 7-12 ms-1, peaking mostly at 900 hPa. The moisture transport for each NLLJ shows that, in addition to the intense local moisture sources, Argentina and Brazil-S NLLJs receive moisture from the tropical-subtropical South Atlantic Ocean and the Amazon basin, while tropical-subtropical South Atlantic Ocean is the main moisture source for Brazil-SE NLLJ. Both moisture sources and sinks are stronger during the austral summer and fall. Brazil-NE NLLJ receives moisture from the tropical South Atlantic Ocean, which has weak seasonality. The moisture sources for Brazil-N and Venezuela NLLJs come from the tropical North Atlantic Ocean during the austral summer and fall, while the tropical South Atlantic Ocean appears as an additional moisture source in the austral winter. This research contributes to improving our understanding of the NLLJs and their role in transporting moisture and controlling precipitation over the continent according to the season of the year, helping to improve the seasonal climate forecasting.